2004
DOI: 10.1002/ps.845
|View full text |Cite
|
Sign up to set email alerts
|

Turfgrass management and weed control without pesticides on football pitches in Denmark

Abstract: Management of turfgrass on football pitches without pesticides involves a considerable challenge for weed control. By improving conditions for grass growth by cultural practices, weeds may be repressed by stronger competition from the grass. A 3-year field trial on 37 football pitches investigated the effects of various cultural management practices on percentage grass, weed and bare ground, respectively. The trial included twelve different treatments, comprising different combinations of fertiliser level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 3 publications
2
47
0
Order By: Relevance
“…Increasing public concerns about pesticide use in urban environments have prompted research in alternative approaches (Hatcher & Melander 2003; Larsen, Kristoffersen & Fischer 2004). Although cultural management techniques can reduce dependency on chemical herbicides and fertilizers, they do not provide reliable broadleaf weed control (Busey 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing public concerns about pesticide use in urban environments have prompted research in alternative approaches (Hatcher & Melander 2003; Larsen, Kristoffersen & Fischer 2004). Although cultural management techniques can reduce dependency on chemical herbicides and fertilizers, they do not provide reliable broadleaf weed control (Busey 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Even though time was minimal for re‐establishment, the strategy is to get as close to 100% turf stand as possible. Larsen et al (15) made conclusions from F values, and found the highest F values were associated with ground cover before the start of a playing season.…”
Section: Turfgrass Cover Percentmentioning
confidence: 99%
“…Even though time was minimal for re-establishment, the strategy is to get as close to 100% turf stand as possible. Larsen et al (15) made conclusions from F values, and found the highest F values were associated with ground cover before the start of a playing season. Mowing treatments (started on 25 June 2002 and 3 July 2003, respectively) had approximately a 35-day window compared to fertilizer treatments applied at the beginning of the 70-day re-establishment window.…”
Section: Turfgrass Cover Percentmentioning
confidence: 99%
“…However, integrating control practices emphasizes the use of multiple strategies to address the causes of weed fitness, (Buhler 2002). Consequently, investigating for alternative cultural and biological practices has intensified (Hatcher and Melander 2003; Larsen et al, 2004). Biological strategies recommended alternatives to the application of chemicals that provide new environmental options weed control practices (Bailey andMupondwa 2006, Boyetchko 2005).…”
Section: Introductionmentioning
confidence: 99%